Near binocular visual function in young adult orthokeratology versus soft contact lens wearers. Issue 3 (June 2017) - Gifford, Kate; Gifford, Paul; Hendicott, Peter L.; Schmid, Katrina L.
Highlights: Young myopic adults wearing OK show more exophoria than matched SCL wearers. These long term OK wearers also show a lower accommodative lag than SCL wearers. These findings have relevance to visual acceptance and myopia management. Abstract: Purpose: To compare near point binocular vision function of young adult myopes wearing orthokeratology (OK) lenses to matched single vision soft disposable contact lens (SCL) wearers. Methods: A retrospective clinical record analysis of all OK wearers (18–30 years) presenting over an 18 month period was undertaken. Data was extracted for 17 OK wearers, with 17 SCL wearers matched for age, refractive error and duration of contact lens wear. Binocular vision data included horizontal phoria (phoria), horizontal base-in (BIFR) and base-out fusional reserves (BOFR) and accommodation accuracy (AA). Results: The OK group was 25.8 ± 3.2 years, with a duration of wear of 45.7 ± 25 months and refractive error of R −2.09 ± 1.23D, L −2.00 ± 1.35D. Compared to matched SCL wearers the OK group were significantly more exophoric (OK −2.05 ± 2.38Δ; SCL 0.00 ± 1.46Δ, p = 0.005) and had better accommodation accuracy (OK 0.97 ± 0.33D; SCL 1.28 ± 0.32D, p = 0.009). BIFR and BOFR were not different in the two groups. Frequency histograms showed that more SCL wearers had high lags of accommodation (AA ≥ 1.50D: 8 SCL, 2 OK) and esophoria (≥1Δ: 5 SCL, 1 OK) than OK wearers. A positive correlation was found between refraction and phoria in the SCL group (r = 0.521, p = 0.032). Conclusion: Young adult myopes wearing OK lenses display more exophoria and lower accommodative lags at near compared to matched single vision SCL wearers. Young adult myopes with specific binocular vision disorders may benefit from OK wear in comparison to single vision SCL wear. This has relevance to both the visual acceptance of OK lenses and in managing risk factors for myopia progression.